Risk Factors of Road Traffic Accidents (RTA) in context of Bangladesh (Journal of Dhaka Medical College, 2010)
Objective: To explore the risk factors related to road traffic accident in context of Bangladesh. Design: This was a cross sectional type of descriptive study. Settings: The study was conducted at emergency and casualty department of Dhaka Medical College Hospital (DMCH) and Sir Salimullah Medical College (SSMC) & Mitford Hospital, Dhaka respectively. Study Period: The study was conducted from July 2007 to June 2008. Subjects: A total of 400 Road Traffic Accident (RTA) patients attended during data collection period of 3 months at Dhaka Medical College and Sir Salimullah Medical College (SSMC) & Mitford Hospitals were consider as the study population. Result: This study included 400 Road Traffic Accident (RTA) patients. Among them, 23.8% patients due to accidents were related to truck accidents followed by bus (20.3%) and CNG Taxi (11.3%) respectively It has been revealed that frequency of accidents caused by new vehicles and old vehicles were almost equal (36.5%) and 13.5% vehicle were overloaded when accidents happened. Fast speeds of the vehicles (62%) were responsible for accidents. About 31% stated that even with normal speed accident was happened. About 44.8% accidents were caused due to collision with other vehicles as stated by the patients. Majority of the patients (52.8%) stated that drivers were looked healthy, 17.8% drunker and 5.5% looked drowsy when they drove vehicles during accident. Majority (55%) of them drove in wrong side of the road. In 78.3% cases, there was no traffic signal and though available, 39.1% driver did not follow traffic signal. About 25% patients stated that defective road is the factor of causation of accidents. Majority (76.75%) of the patients opined that accident was happened during day time and in sufficient light (66%). Weather was foggy stated by 16% patients. Only 6.75% victims used protective measure during accidents. Conclusion: This study was conducted with a view to explore the risk factors related to road traffic accident. Nevertheless, it is not feasible to draw a concrete conclusion. But on the basis of this study findings, it may be stated that a greater part of Road Traffic Accidents (RTA) can be prevented by specific preventive measures and also taking personal precautions. It is also to be concluded that countywide wide mass scale study should be carried out in this specific emerging field to combat road traffic accidents as a major public health issue. Key words: Road traffic accidents (RTA); Risk Factors. DOI: 10.3329/jdmc.v18i2.6279 J Dhaka Med Coll. 2009; 18(2) : 161-165